2015
DOI: 10.5665/sleep.4414
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nasal Surgery on Continuous Positive Airway Pressure Device Use and Therapeutic Treatment Pressures: A Systematic Review and Meta-Analysis

Abstract: Isolated nasal surgery in patients with OSA and nasal obstruction reduces therapeutic CPAP device pressures and the currently published literature's objective and subjective data consistently suggest that it also increases CPAP use in select patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
96
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 134 publications
(104 citation statements)
references
References 45 publications
5
96
0
1
Order By: Relevance
“…For example, nasal dilators may reduce the pressure required for continuous positive airway pressure (CPAP) devices [32]. Since lower CPAP treatment pressures often improve CPAP use [8], it is possible that nasal dilator use may also improve CPAP use. In those patients with significant improvement in breathing with nasal dilators but who cannot tolerate the devices, site directed nasal surgery may be considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, nasal dilators may reduce the pressure required for continuous positive airway pressure (CPAP) devices [32]. Since lower CPAP treatment pressures often improve CPAP use [8], it is possible that nasal dilator use may also improve CPAP use. In those patients with significant improvement in breathing with nasal dilators but who cannot tolerate the devices, site directed nasal surgery may be considered.…”
Section: Discussionmentioning
confidence: 99%
“…There are many treatments for OSA, to include medical management with positive airway pressure devices [4], oral appliances, and myofunctional therapy [5]. Nasal therapies to help treat OSA include nasopharyngeal airway stenting devices [6], nasal expiratory positive airway pressure devices (Provent) [7], and nasal surgery [8, 9]. …”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of 18 articles with 279 patients concluded that the mean CPAP requirement decreased postoperatively (11.6 ± 2.2 to 9.5 ± 2.0 cm H 2 O, P < .00001) and that 89% of patients who were not using CPAP regularly subsequently accepted or adhered to CPAP use after their nasal surgery. 88 During the immediate postoperative period, nasal packing-if it is used (since routine nasal packing is not recommended-see key action statement 9-can worsen upper airway resistance and complicate the management of OSA. Friedman et al demonstrated that, among patients with mild OSA, the AHI significantly increased with nasal packing.…”
Section: Supporting Textmentioning
confidence: 99%
“…A large proportion of these were investigations of different modalities and treatment arms for pediatric tonsillectomy (pediatric studies made up 32.2% of all surgical studies). This relative lack of clinical trials exploring surgical treatments of adult OSA is concerning, especially with increasing literature demonstrating the benefit of surgical therapy for OSA . In the future, it is important that surgical options remain an available and investigated part of OSA management.…”
Section: Discussionmentioning
confidence: 99%
“…This relative lack of clinical trials exploring surgical treatments of adult OSA is concerning, especially with increasing literature demonstrating the benefit of surgical therapy for OSA. 5,18,19 In the future, it is important that surgical options remain an available and investigated part of OSA management. This finding of a minor role for ear, nose, and throat specialists in sleep apnea research is consistent with several prior recent studies expressing concern about the diminishing role of our specialty in OSA care.…”
Section: Discussionmentioning
confidence: 99%